Silence of lncRNA MIAT protects ATDC5 cells against lipopolysaccharides challenge via up-regulating miR-132 - Chen Li (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The over-expanding role of lncRNA myocardial infarction associated transcript (MIAT) in various human diseases has been recently revealed. This study attempted to see the role of MIAT in a cell model of osteoarthritis (OA). ATDC5 cells were subjected to lipopolysaccharides (LPS) to mimic a cell model of OA. The effects of MIAT on the model were tested by performing CCK-8 assay, flow cytometry, qRT-PCR, western blot and ELISA. The downstream miRNA and signalling pathways were studied by utilizing qRT-PCR and western blot. Transfection of ATDC5 cells with the shRNA specific against MIAT significantly attenuated LPS-evoked apoptosis and cytokines release. At the meantime, the viability loss and the cleavage of caspases were ameliorated as well. MIAT overexpressed lead to the opposite result. Further, miR-132 was found to be negatively regulated by MIAT. The protective effects of MIAT silence were flattened when miR-132 expression was suppressed. Besides that the inhibitory effects of MIAT silence on LPS-evoked NF-κB and JNK activation were eliminated by miR-132 silence. This study illustrated that silence of MIAT protected ATDC5 cells against LPS challenge. The chondroprotective effects of MIAT silence may be via up-regulation of miR-132 and inhibition of NF-κB and JNK pathways.